ICU survivor’s facing with risk of cardiovascular and respiratory problem: What should you do as healthcare provider? - Jamaludin, Thandar Soe Sumaiyah (2017)
The risk of cardiovascular and respiratory events after admitted to ICU is not known, and these events may explain increased long-term mortality in survivors of ICU patients. Mobility is the best medicine in Managing of critical illness survivors with cardiovascular & respiratory problem.